Pengaruh Motivasi Internal Dan Eksternal Terhadap Kinerja Kader Dalam Program Gebrak ( Gerakan Bersama Amankan Kehamilan Dan Persalinan) Di Wilayah Puskesmas Blabak Kabupaten Kediri - Triatmi Andri Yanuarini; Reni Triwahyuningsih (coba, 2016)
High risk pregnancy is a condition where the condition of pregnant women can cause the fetus not grow in a healthy, even death in the mother and fetus. Based on data from Kediri District Health Office in 2014 amounted to 28 187 pregnant women, while the high-risk pregnant women amounted to 5637 people (20%). Number of high risk pregnant women most at Puskesmas Blabak number of 249 people with a total cadre 110 people. Scope K1 96.2% (100%), K4 coverage 92% (95%), high-risk detection by the public 13.77% (20%), Bumil Risti handled 18.7% of health workers (20%), obstetric complications which handled 87% (80%), Assisted by health workers health facility 93% (95%). Rewards and motivation to the Posyandu cadres is very important, especially cadres escort high-risk pregnant women. In the course of the RBM awards are expected to further spur the cadres to participate in social work in order to press AKI, so that cadres can increase each year. The design used in this study is a survey research. Judging from the nature of this survey is a survey that is explanotory survey to test the truth of a hypothesis to explain the causal relationship between variables. Data collected by cross sectional namely data collection throughout the study subjects were collected directly from the respondents through kuesioner.Analisa data in this study using the program, namely Smart PLS structural equation modeling with a relatively small sample size and not membuhkan multivariate normal assumption. The results of the study are not any effect on the performance of internal motivation of cadres in the RBM program. No external motivation influence on the performance of cadres in the RBM program. External motivation has the greatest influence on the performance of cadres in the RBM program. From the results of this study are expected Department of Health and the village is expected to provide additional incentives for cadres accompanying high risk pregnant mothers. Keywords: Motivation, cadres